PERFORMANCE ANALYSIS OF SOLAR WATER HEATER FOR THE OPTIMAL TILT ANGLE AT DIFFERENT FLOW RATES BY USING FLAT PLATE COLLECTOR - Markndeyulu Vuggirala; N. Alagappan; CH V K N S N Moorthy; N.V. Narasimrao Rao (Proceedings on Engineering Sciences, 2025)
The goal of the current work is to investigate the performance characteristics of solar flat plate collectors at various tilt angles. One of the most significant solar energy-capturing devices is the flat plate collector, which runs on either water or air. The very simple flat plate solar collector is the most widely used of the numerous solar collector ideas now under development. Its features are well-known, and when weighed against other collector varieties, it is the simplest and least costly to build, install, and operate. Furthermore, it can employ sun radiation in both diffuse and direct beam forms. Flat plate collectors can generate heat at high enough temperatures for buildings, domestic hot water, and swimming pools, both for home and commercial use. This paper evaluates the performance of flat plate solar collectors for solar water heating system were tested. The efficiencies for the collectors are tested at different flow rate (60kg/hr,90kg/hr,120kg/hr) and at different tilt angles (150,300,450). The method has been verified through comparison with the experimental data. Based on the measured efficiencies, the efficiencies for the collectors as functions of flow rate and tilt angle are obtained. The calculated efficiencies are in good agreement with the measured efficiencies.